Introduction to Structural Chemistry - Batsanov, Stepan S.; Batsanov, Andrei S.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
Structural chemistry often suffers from fragmented approach, progressing either from the aggregate state (crystallography vs isolated molecule structure), from the method of investigation (X-ray diffraction, spectroscopy, compressibility, etc.) or from the type of substances (inorganic, organometallic, organic). The present book attempts to bridge these gaps, linking the properties of atoms, radicals, molecules, clusters, nano-particles, liquids, solutions, melts, glasses and crystalline solids. Geometrical structure is considered in its indissoluble unity with energetic properties and polarisability (and hence optical properties), using electronegativity as a unifying concept. Recent decades brought abundant and more precise structural measurements, as well as opening of whole new areas, e.g. non-classical crystals, high-pressure crystallography, real-time study of phase transitions, nanomaterials with their intricate size-effects, fullerenes and clusters, van der Waals molecules. The book gives an outline of these new developments, while showing that the old concepts and techniques, from atomic radii to refractometry, are still useful. Features: A survey of structural chemistry across different aggregate states (gas, liquid, glass, crystalline, nano-materials) Conceptual and numerical links between geometrical, thermodynamic, electronic and optical properties Up-to-date reference data, systematically presented and tabulated Critically revised tables of standard parameters - bond distances and energies, atomic radii, equations of state, etc.
Keywords: Medicine; Physical chemistry; Atomic structure; Molecular structure; Spectra; Solid state physics; Crystallography; Nanoscale science; Nanoscience; Nanostructures; Biomedicine; Biomedicine general; Physical Chemistry; Crystallography; Nanoscale Science and Technology; Atomic/Molecular Structure and Spectra; Solid State Physics; Electronic books